IMPLEMENTATION OF MODERN PEDAGOGICAL TECHNOLOGIES IN THE PROCESS OF ORGANIZING STUDENTS' INDEPENDENT ACTIVITIES (World Bulletin of Social Sciences, 2021)
Purpose of the study. Currently, the issues of information of education and the use of information technologies in the educational process are receiving new development. At the same time, high-quality training of future lecturers is possible only if innovative methods are used in the process of their training, reflecting modern, activity-based approaches to the organization of the educational process, forms of educational work, and also assessment methods. In this connection, the aim of the study was to find one of the solutions to the organization of independent work of students of a pedagogical institute using active and interactive learning technologies within the educational information environment of the university, as well as testing the identified innovative methods using distance learning technologies. Materials and methods . To resolve this problem, the authors of the article carried out the analysis of pedagogical literature, practical experience in organizing student learning, as well as self-analysis of the use of distance learning technologies in the process of teaching bachelors in the direction of preparation “Pedagogical Education”, followed by a generalization and systematization of the identified features. The study made it possible to distinguish three areas of educational and informational interaction within the framework of organizing and supporting students' independent work, namely, cloud technologies, social networks and distance learning technologies, as well as identify the strengths and weaknesses of each of the areas. At the same time, it is determined that the use of distance educational technologies has the greatest number of advantages
Keywords: materials; methods; logically; accurately